2007
DOI: 10.1007/s12088-007-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and mutation analysis of family 11, Carbohydrate-Binding Module (CtCBM11) of cellulosomal bifunctional cellulase from Clostridium thermocellum

Abstract: The non-catalytic, family 11 carbohydrate binding module (CtCBM11) belonging to a bifunctional cellulosomal cellulase from Clostridium thermocellum was hyperexpressed in E. coli and functionally characterized. Affi nity fi electrophoresis of CtCBM11 on nondenaturing PAGE containing cellulosic polysaccharides showed binding with β-glucan, lichenan, hydroxyethyl cellulose and carboxymethyl cellulose. In order to elucidate the involvement of conserved aromatic residues Tyr 22, Trp 65 and Tyr 129 in the polysaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…3) It has been reported that CjCBM3 is not able to bind oat-spelt xylan, whereas CtCBM11 and CsCBM6 do. [11][12][13][14] The affinity of CtCBM11 and CsCBM6 to oat-spelt xylan is 1.7 × 10 1 M −1 and 2.3 × 10 6 M −1 , respectively. [12][13][14] This suggests that the quite low affinity of CtCBM11, which should cause low binding of CtCel5E-CtCBM11 to oat-spelt xylan, confers a small increase in CtCel5E activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3) It has been reported that CjCBM3 is not able to bind oat-spelt xylan, whereas CtCBM11 and CsCBM6 do. [11][12][13][14] The affinity of CtCBM11 and CsCBM6 to oat-spelt xylan is 1.7 × 10 1 M −1 and 2.3 × 10 6 M −1 , respectively. [12][13][14] This suggests that the quite low affinity of CtCBM11, which should cause low binding of CtCel5E-CtCBM11 to oat-spelt xylan, confers a small increase in CtCel5E activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The replacement of any of these residues by alanine resulted in decreased binding of carboxymethylcellulose (CMC), β‐glucan, glucomannan, and xylan. The highest effect was observed with the W65A mutant, whereas lesser impacts are observed with the Y129A and Y22A mutants …”
Section: Importance Of Aromatic Amino Acid Residues For Carbohydrate mentioning
confidence: 91%
“…Native polyacrylamide gels were prepared consisting of 7.5% (w/v) acrylamide in 25 mM Tris/250 mM glycine buffer [5]. The substrates (1.0%) were added to the polyacrylamide mixture before polymerization.…”
Section: Affi Nity Electrophoresis Of Lichenasementioning
confidence: 99%
“…A bifunctional cellulase from Clostridium thermocellum was shown to contain an N-terminal family 26 glycoside hydrolase called lichenase (Lic26A) [2] and an internal family 5 glycoside hydrolase (GH5) [3] catalytic domains and a C-terminal family 11 carbohydrate-binding module (CBM11) [4,5]. It was demonstrated that the carbohydratebinding module (CBM11) of bifunctional cellulase binds to ligands that are substrates for both Lic26A and GH5 catalytic modules [4].…”
Section: Introductionmentioning
confidence: 99%